Hubungan Status Gizi dan Usia Menarche Dengan Dismenore Primer pada Remaja Putri - Suriani Beddu; Sitti Mukarramah; Viqy Lestahulu (AIPKIND (Asosiasi Pendidikan Kebidanan Indonesia), 2015)
Primary dysmenorrhea is a problem in the field of gynecology that affects many adolescent girls. The impact of adolescent dysmenorrhea can interfere with the activity and lead to students to abstain from schools. Abnormal nutritional status and age of menarche are a risk factor of rapid primary dysmenorrhea. This study aimed to determine the relationship of nutritional status and age at menarche to primary dysmenorrhea in high school girls in Makassar National High School from May to Juny 2013. The population was 98 students and the sample size was 79 people using Solvin formula with standard error of 0.05 with simple random sampling. This was an analytical survey with a cross sectional study design. Data collection used checklist sheet which contained numeric rating scale and anthropometric measurements (stature and weight). Analysis of the data used univariate and bivariate analysis with chi-square test. From the research, the nutritional status variables using chi-square test statistic with pearson chi-square revealed a p-value of 0.008, meaning that there was a significant relationship between nutritional status and primary dysmenorrhea. Statistical test results for the variable of age of menarche showed a p-value of 0.006, meaning that there was a significant relationship between age of menarche and primary dysmenorrhea.